2009
DOI: 10.1111/j.1365-3059.2008.01935.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic spread of Pseudomonas savastanoi pv. savastanoi in olive explants

Abstract: The manner in which the bacterium Pseudomonas savastanoi pv. savastanoi ( Pss ), the causal agent of knot disease, infects olive plants is erratic and has not been fully documented. To investigate the process of Pss invasion, olive explants were inoculated in vitro and examined visually and by light microscopy at 2-weekly intervals for 10 weeks. In all host genotypes tested, interaction with the pathogen resulted in: (i) a progressive collapse of the stem, originating at the inoculation site at the apex of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…As far as P. savastanoi is concerned, sanitary certification programs for olive and oleander mother plants and propagation materials already started in many countries [41,51,52], but the presence of Psv and Psn on these plants is still assessed mainly by visual inspection, looking for the typical hyperplastic knots. On the other hand, it was clearly demonstrated that the spread of the disease can also occur with asymptomatic propagation materials, where these bacteria can be found either as endophytes or as epiphytes [37,38,53-55]. Hence innovative detection protocols for P. savastanoi pathovars, which have very low detection limits and are able to obtain good results in vivo , are strongly needed and can be achieved only by PCR-based methods.…”
Section: Discussionmentioning
confidence: 99%
“…As far as P. savastanoi is concerned, sanitary certification programs for olive and oleander mother plants and propagation materials already started in many countries [41,51,52], but the presence of Psv and Psn on these plants is still assessed mainly by visual inspection, looking for the typical hyperplastic knots. On the other hand, it was clearly demonstrated that the spread of the disease can also occur with asymptomatic propagation materials, where these bacteria can be found either as endophytes or as epiphytes [37,38,53-55]. Hence innovative detection protocols for P. savastanoi pathovars, which have very low detection limits and are able to obtain good results in vivo , are strongly needed and can be achieved only by PCR-based methods.…”
Section: Discussionmentioning
confidence: 99%
“…This compound may also play a role in the defence response of olive tree to P. savastanoi infection (Cayuela et al 2006). Phenolic and/or polysaccharidic compounds have been shown to accumulate in outgrowths and xylem vessels of infected olive explants possibly as a reaction to hinder infections (Marchi et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Bacterial cells in knots were shown to be able to migrate, infecting new wounds in plants (secondary infections) (Penyalver et al 2006). A recent histological investigation on the systemic spread of P. savastanoi in olive explants (Marchi et al 2009) described an interaction between O. europaea and P. savastanoi that closely resembles the formation of knots in vivo. The bacterium was also located in xylem vessels of the explants, suggesting a capacity for systemic invasion and induction of secondary infections in different parts of the plants.…”
Section: Introductionmentioning
confidence: 99%
“…They are growing quickly and turn into smooth, soft, spherical "knots" (3-5 mm in diameter) that are covered with greenish bark. With age, the galls grow bigger and became hard, brown to black and corrugated, with a size ranging from a few millimetres to several centimetres in diameter [9]. The development of these galls is dependent on bacterial production of the phytohormone indole-3-acetic acid (IAA) and cytokinins [13].…”
Section: Introductionmentioning
confidence: 99%
“…Olive knot spreads systemically through olive tissue along the xylem vessels, and there is currently a risk that nurseries may grow and trade olive plantlets that harbour the olive knot pathogen [9]. Actually, P. syringae subsp.…”
Section: Introductionmentioning
confidence: 99%